Participatory Design in Suicide Prevention: A Qualitative Study of International Students' Experiences of Adapting the LivingWorks safeTALK Programme - Samuel McKay; Christina Ng; Bridget Kenny; Rafi Armanto; Michelle Lamblin; Jo Robinson (Wiley, 2024)
ABSTRACT Background Current suicide prevention approaches are not adapted to international student needs, and participatory design is a method that may facilitate the development or adaptation of appropriate programmes for this group. Methods This qualitative study investigated the experiences of international university students studying in Australia who participated in a co‐consultation process to adapt the LivingWorks safeTALK suicide prevention programme. Eight international students from the co‐consultation workshop completed semi‐structured interviews about their workshop experience. The data were analysed using reflexive thematic analysis. Results The findings showed that participants found the co‐consultation process empowering and engaging. They also reported that the experience promoted mutual learning and challenged simplistic views of suicide. No students reported experiencing distress. Suggestions for improving participatory design for international students focussed on enhancing participant interaction, supporting quiet voices to be heard and ensuring understanding of mental health and suicide through shared language. Conclusions This study underscores the value of participatory design in suicide prevention, emphasising its potential to empower international students and facilitate culturally sensitive programme adaptations. Patient or Public Contribution International students were involved in the co‐consultation process to redevelop the training content and provided a series of recommendations for improving such processes for international students in the future. The two researchers who conducted the interviews and data analysis were former international students.